Geocronologia U-Pb em zircão detrítico e proveniência de arenitos pré-cambrianos da região de Itupiranga-PA - GOMES, Rafael Neto Silva (2021)
In the Santa Teresinha of Tauri Village, Itupiranga-PA, nearly 100 km to the south of Tucuruí's Hydroelectric Power Plant, occur red-purplish interspersed sandstones and polimitic conglomeratic brecchias. These successions have been attributed to the Tucuruí Group, related to the Gorotire Formation and also to the Uatumã Vulcanism. These deposits occur between the Paleoproterozoic Bacajá Domain (Amazonia Craton) and the Araguaia Belt (Neoproterozoic). The lack of detailed studies of this sedimentary succession makes it challenging to understand its geological context and to infer correlation with geologic units that occurs in this region. Therefore, this work presents U-Pb age data in detrital zircon combined with sedimentological and petrographic data to investigate provenance patterns that allow discussing the origin and geological implications of these deposits. The sedimentary facies profile described nearby the Tocantins River comprises coarse-to medium-grained sandstones planar cross-bedding (At) and trough cross-bedding (Aa), massive gravel (Gm), planar cross-bedding conglomeratic brecchia (Bt) and medium-grained sandstones with planar lamination (App). This facies association is interpreted as related to braided/gravel-bed rivers within an alluvial system. Paleocurrent measurements point to a general trend towards ENE, which indicates sources west of the current location. The sandstones and gravels have very low textural and mineralogical maturity and are composed of grains from different rock fragments (granites, mylonites, volcanic, BIF's, quartzites, etc.), quartz and feldspar. The U-Pb ages of the detrital zircons analyzed showed a mainly Rhyacian contribution with grains around 2.0-2.1 Ga with lesser contributions from Neoarchean to Siderian (2.5-2.4 Ga) and Mesoarchean (around 3.0 Ga). Few zircon grains with 207Pb/206Pb ages of 1.8-1.9 Ga may be slightly older. The geochronological data suggest a maximum depositional age probably around 2.0-2.1 Ga. Based on these data, the Itupiranga sedimentary deposits described here possibly do not represent an extension of the Tucuruí Group, as previously suggested. Correlations with the deposits described in the northeastern portion of the Carajás Mineral Province and the occurrence of 2.1-2.0 Ga pull-apart basins in the Bacajá Domain and surroundings, related to Transamazonian collision, are suggested here. However, further studies, to a greater extent, are recommended to validate this hypothesis.